Evaluation of web reinforcements in prestressed concrete box girders through shear-transverse bending domains. Issue 8 (June 2021) - Granata, Michele Fabio; Recupero, Antonino
In concrete box girders, the amount and distribution of reinforcements in the webs have to be estimated considering the local effects due to eccentric external loads and cross-sectional distortion and not only the global effect due to the resultant forces of a longitudinal analysis: shear, torsion and bending. This work presents an analytical model that allows designers to take into account the interaction of all these effects, global and local, for the determination of the reinforcements. The model is based on the theory of stress fields and it has been compared to a 3D finite element analysis, in order to validate the interaction domains. The results show how the proposed analytical model allows an easy and reliable reinforcement evaluation, in agreement with a more refined 3D analysis but with a reduced computational burden.